Pengaruh Times Interest Earned Ratio, Total Asset Turnover dan Perputaran Modal Kerja terhadap Profitabilitas pada Perusahaan Sub Sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesia periode 2013-2017 - Yunita Yunita; Shelly Shelly; Novia Ariani; Erline Chandra; Selvia Selvia; Afrizar Pane; Surya Kelana Putra (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2019)
This research was conducted with the aim of testing and analyzing how the influence of times interest earned ratio, total asset turnover and working capital turnover on profitability both simultaneously and partially in property and real estate companies listed on the Indonesia Stock Exchange in 2013-2017. The research method used in this study is a quantitative research approach, the type of research is associative or relationship and the nature of research is a causal relationship. The population in this study were all property and real estate companies listed on the Indonesia Stock Exchange in 2013-2017. Withdrawal of the study sample using purposive sampling technique, so that the research sample obtained as many as 90 observation observations. Data analysis method used in this study is the classic assumption test and multiple linear regression analysis with the SPSS program. The results of this study indicate that simultaneously times interest earned ratio, total asset turnover and working capital turnover have a significant effect on profitability. Partially, times interest earned ratio and total asset turnover have a significant effect on profitability while time working capital turnover has no effect on profitability. The test results of the coefficient of determination obtained by the value of R Square of 0.502, which means that the influence of times interest erned ratio, total asset turnover and working capital turnover on profitability in property and real estate companies listed on the Indonesia Stock Exchange in 2013-2017 is 50.2%, while the remaining 49.8% is influenced by other factors.